A rare case: Vena cava inferior agenesis with aberrant hepatic vein in an asymptomatic patient - Kalayci, T. O.; Karasu, S.; Demir, R. O.; Apaydin, M.; Erdogan, N. K.; Oyar, O. (Phlebologie, 2014)
Inferior vena cava agenesis is a rare anomaly in an asymptomatic patient. A 58-year-old female patient with complete absence of the inferior vena cava and aberrant right hepatic vein is presented with radiologic findings. To our best knowledge, such a combination of venous anomalies has not previously been documented in the literature and this is the first case in the literature due to the coincidence of total inferior vena cava agenesis with aberrant hepatic vein.
Keywords: Multidetector computed tomography; angiography; colour doppler ultrasound; agenesis; inferior vena cava